2019
DOI: 10.1186/s12889-019-8114-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Anemia among women in Uganda: further analysis of the Uganda demographic and health surveys

Abstract: BackgroundAnemia is a public health problem in many developing countries. It affects a sizable proportion of women of reproductive age. Anemia increases the risk of morbidity and mortality from infectious diseases, and can lead to poor fetal outcomes, and low productivity. This study examined the trends and determinants of anemia among women of reproductive age in Uganda.MethodsThis study analyzed data from the Uganda Demographic and Health Surveys conducted in 2006, 2011, and 2016. The study was based on 10,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
30
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 25 publications
32
30
4
Order By: Relevance
“…In addition, obtaining education may help women adopt appropriate lifestyle patterns such as better health-seeking habits as well as hygiene practices that can prevent women from getting anemia. Consistent with other studies conducted in different settings [20,21,29,30,36,60], in this study, being from second to highest household wealth quantiles were associated with lower prevalence of anemia as compared with women from households with lowest quantile. This could be due to improved socioeconomic status is associated with healthy nutrition, lower infection/morbidity, and increased access and utilization of medical health services [59,61,62].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, obtaining education may help women adopt appropriate lifestyle patterns such as better health-seeking habits as well as hygiene practices that can prevent women from getting anemia. Consistent with other studies conducted in different settings [20,21,29,30,36,60], in this study, being from second to highest household wealth quantiles were associated with lower prevalence of anemia as compared with women from households with lowest quantile. This could be due to improved socioeconomic status is associated with healthy nutrition, lower infection/morbidity, and increased access and utilization of medical health services [59,61,62].…”
Section: Discussionsupporting
confidence: 92%
“…Even though anemia affects all countries, it mostly affects LMICs especially Asian and Sub-Saharan African countries which accounts for 89% of the anemia burden [19]. In eastern Africa, the prevalence of anemia in women of reproductive age is higher, which ranges from 19.2% in Rwanda to 49% in Zambia [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is the most prevalent disease in Africa and Asia affecting the males, females and children of all ages and having detrimental effects on their health. Frequency of anemia in our study is 56.8%, Faseeh 7 observed 66.8%, Olivia reported 32% in Uganda 9 and World Health Organization described that anemia affects 35% of Africal population. 4 Indian State-level Disease Burden Initiative Malnutrition Collaborator described that 54.5% of females were between 15-49 years of age.…”
Section: Discussionsupporting
confidence: 46%
“…3 Olivia stated that poor household is indicator of poverty and the poverty leads to more prevalence of anemia. 9 Bekele concluded that pregnant females with low income were four times more likely to develop anemia than high income group. 3 We observed that majority of females (81.95%) never practiced or infrequently practiced contraception.…”
Section: Discussionmentioning
confidence: 99%
“…is finding was similar to reports in developing countries like Ethiopia, Uganda, and South Asia. [27][28][29]. is might be due to the fact that having a low income would mean having less money to buy iron-containing nutritious foods or have a balanced diet.…”
Section: Discussionmentioning
confidence: 99%